Stability analysis of a tall building with mat foundation over sandy soil with soil-structure interaction approach - Mg , Thiha Zaw; Khin , Than Yu (2008)
This paper presents the stability analysis of a tall building with mat foundation founded on liquefaction susceptible soil during design earthquake. The stability of a structural foundation and structure itself is mainly depends on the bearing capacity of underlying soil during and after earthquake. Since modulus of subgrade reaction or stiffness of the soil is a conceptual relation between the soil pressure and deflection, it can be changed with fluctuation of net allowable bearing capacity of underlying soil. Bearing capacity of the soil can also be changed according with the value of liquefaction potential. The loss of spring stiffness occurred more or less depending on degree of liquefactions. Modification of localized spring stiffness of the foundation is carried out by numerical method. For a typical 2 unit 10 storey building, the stress states were chosen at a depth of 12 ft. It belongs to seismic zone 2A. ETABS software is used as a design aid for performance of numerical completion for the analysis of model. The focus of this paper is to study the influence of liquefaction potential on modifying spring stiffness of the soil under the building and potential failure modes of the building to be considered in soil structure interaction.